Virus Diseases of Vegetable and Melon Crops in the South of the Russian Far East - V. F. Tolkach; N. N. Kakareka; Yu. G. Volkov; Z. N. Kozlovskaya; M. V. Sapotskiy; T. I. Pleshakova; K. P. D'yakonov; M. Yu. Shchelkanov (Юг России: экология, развитие, 2020)
Aim. The development of an inventory of phytoviruses affecting vegetable and melon crops in the South of the Russian Far East.Discussion. On the basis of many years of original research, carried out on a regular basis by the Laboratory of Virology (Federal Scientific Centre of East Asia Biodiversity, Far Eastern Branch, Russian Academy of Sciences) since 1962 as well as available data in the literature, information about the symptoms of diseases, circulation, reserve plants and vectors are presented for the alfalfa mosaic virus (Bromoviridae, Alfamovirus); tomato aspermy virus and cucumber mosaic virus (Bromoviridae, Cucumovirus); cauliflower mosaic virus (Caulimoviridae, Caulimovirus); garlic mosaic virus (Potyviridae, Carlavirus); tobacco etch virus, allium yellow dwarf virus, bean yellow mosaic virus, watermelon mosaic virus 2, turnip mosaic virus and bean common mosaic virus (Potyviridae, Potyvirus); radish mosaic virus (Picornavirales, Secoviridae, Comovirus); tobacco ringspot virus (Picornavirales, Secoviridae, Nepo-virus); cucumber green mottle mosaic virus, tobacco mosaic virus and tomato mosaic virus (Virgaviridae, Tobamovirus).Conclusion. The information presented forms the basis for the development of a set of diagnostic test systems for phytovirus diseases of vegetable and melon crops; a necessary element of activities directed to the improvement of food productivity and security of the Russian Federation in the Far East.